2007
DOI: 10.1523/jneurosci.4072-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Distribution of Odorant-Evoked Activity in the Piriform Cortex

Abstract: Despite a remarkably precise spatial representation of odorant stimuli in the early stages of olfactory processing, the projections to the olfactory (piriform) cortex are more diffuse and show characteristics of a combinatorial array, with extensive overlap of afferent inputs and widespread intracortical association connections. Furthermore, although there is increasing evidence for the importance of temporal structure in olfactory bulb odorant-evoked output, little is known about how this temporal patterning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
183
1
9

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 188 publications
(217 citation statements)
references
References 51 publications
(74 reference statements)
15
183
1
9
Order By: Relevance
“…This matches well with what have been reported from the aPCX of anesthetized animals (Wilson, 2001;Rennaker et al, 2007;Yoshida and Mori, 2007;Poo and Isaacson, 2009;Stettler and Axel, 2009;Isaacson, 2010). Several studies have shown that piriform cortical neurons can be activated by structurally dissimilar odorants (Rennaker et al, 2007;Yoshida and Mori, 2007;Poo and Isaacson, 2009). Similarly, both type I PNs and GABAergic neurons in the aPCX of awake mice are excited by odorants belonging to different chemical groups.…”
Section: Odor Representation By Functionally Heterogeneous Populationsupporting
confidence: 91%
See 3 more Smart Citations
“…This matches well with what have been reported from the aPCX of anesthetized animals (Wilson, 2001;Rennaker et al, 2007;Yoshida and Mori, 2007;Poo and Isaacson, 2009;Stettler and Axel, 2009;Isaacson, 2010). Several studies have shown that piriform cortical neurons can be activated by structurally dissimilar odorants (Rennaker et al, 2007;Yoshida and Mori, 2007;Poo and Isaacson, 2009). Similarly, both type I PNs and GABAergic neurons in the aPCX of awake mice are excited by odorants belonging to different chemical groups.…”
Section: Odor Representation By Functionally Heterogeneous Populationsupporting
confidence: 91%
“…At ϳ300 ms after the opening of final solenoid valve, vigorous firing of action potentials were evoked during the entire period of odorant application (2 s). The spike firing was rhythmic at 4 -5 Hz, suggesting activity coupled to respiratory cycles (Wilson, 1998;Litaudon et al, 2003;Rennaker et al, 2007). Moreover, the responses were reliable across multiple consecutive trials when the same odorant was presented (Fig.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…Olfactory receptors are broadly selective (Katada S et al, 2005), albeit species differences have been reported (Rawson NE et al, 1997), and respond together in a combinatorial way (Rennaker RL et al, 2007;Zou Z, Buck LB, 2006). It is, then, important to complement experiments that use molecular, cellular, and tissue approaches with those that use systemintegrated behavioral approaches.…”
Section: Introductionmentioning
confidence: 99%